2015
DOI: 10.1097/qai.0000000000000429
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Specific ADCC Improves After Antiretroviral Therapy and Correlates With Normalization of the NK Cell Phenotype

Abstract: HAART improves the ability of NK cells to mediate ADCC after 6 months. This improvement does not correlate with general immune restoration, as measured by CD4 T-cell counts, but rather to a decrease in the frequency of NK cells expressing CCR7 and CD27.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
3
12
0
Order By: Relevance
“…It is possible that a shorter duration of ART would be sufficient to accomplish the same improvement in the CD8 + T cell phenotype. For example, we have previously shown that for NK cells, six months of ART is sufficient for a significant restoration of phenotype [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that a shorter duration of ART would be sufficient to accomplish the same improvement in the CD8 + T cell phenotype. For example, we have previously shown that for NK cells, six months of ART is sufficient for a significant restoration of phenotype [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the earlier ART is administered to HIV-1-infected patients, the more pronounced is the recovery of NK cell-mediated ADCC. This immune response reaches its highest peak if the antiviral treatment starts prior to sero-conversion and/or when the CD4 + T cell counts is above 350 cells/μl [120122]. Importantly, the exposure of NK cells to IL-10 has been shown to reproduce an aberrant repertoire of NKRs that is similar to that observed during the course of HIV-1 infection.…”
Section: Nk Cells and Antiretroviral Therapymentioning
confidence: 99%
“…ADCC activity was detected using PanToxiLux (On-coImmunin, Gaithersburg, MD) according to the previously described ADCC-GranToxiLux procedure. 43,44 Env-coated CEM.NKR CCR5 cells 45 were used as target cells and coated 90 min at 4°C with recombinant Env. Env-coated target cells have previously been demonstrated to be equally effective in the ADCC assay as infected target cells, 44 which we confirmed in a separate experiment (data not shown).…”
Section: Adcc Assaymentioning
confidence: 99%